Omega-3 Polyunsaturated Fatty Acids and Their Bioactive Metabolites in Gastrointestinal Malignancies Related to Unresolved Inflammation. A Review - Irún, Pilar; Lanas, Angel; Piazuelo, Elena (Frontiers in Pharmacology, 2019)
Chronic inflammation takes part in the pathogenesis of some malignancies of the gastrointestinal tract including colorectal (CRC), gastric and esophageal cancers. The use of ω3 polyunsaturated fatty acids (ω3-PUFAs) supplements for chemoprevention or adjuvant therapy of gastrointestinal cancers is being investigated in the recent years. Most evidences have been reported in CRC, although their protective role has also been reported for Helicobacter pylori-induced gastric cancer or Barrett’s esophagus-derived adenocarcinoma. Studies based on ω3-PUFAs supplementation in animal models of familial adenomatous polyposis (FAP), as well as in colon and colitis-associated cancers revealed positive effects on cancer prevention, reducing the number and size of tumors, down-regulating arachidonic acid-derived eicosanoids, inhibiting nuclear factor kappa B pathway or upregulating anti-oxidant enzymes. Beneficial effects have also been found in FAP patients. Of special interest is the positive effect on radio- and chemo-sensitivity, specificity and prevention of treatment complications when using ω3-PUFAs supplementation as adjuvant therapeutic strategy. Some controversial results obtained in CRC might be justified by different dietary sources, extraction and preparation procedures of ω3-PUFAs, difficulties on filling out food questionnaires, daily dose and type of PUFAs, adenoma subtype, location of CRC, sex differences and genetic factors. Studies using animal models of inflammatory bowel disease have confirmed that exogenous administration of active metabolites derived from ω3-PUFAs called pro-resolving mediators like lipoxin A4, resolvins derived from eicosapentaenoic (EPA), docosahexaenoic (DHA) and docosapentaenoic (DPA) acids as well as maresin 1 and protectins DHA- and DPA-derived respectively improve disease and inflammatory out-comes without causing immunosuppression nor other side-effects.